Analysis of Maximal Volume of Oxygen for Gorontalo Contingent Martial Arts Athletes - Suprianto Kadir; Arief Ibnu Haryanto; I Kadek Suardika; Nur Rohmah Muktiani (Universitas Negeri Semarang, 2024)
This research analyzes Maximal Volume of Oxygen (VO2 Max) as the main variable to measure the aerobic capacity of martial arts athletes from the Gorontalo Contingent. This variable is important for understanding the level of cardiovascular fitness and physical endurance capabilities of athletes in facing training and competition. This research uses descriptive analytical research methods. The total number of subjects was nine athletes including four Taekwondo athletes, two Wushu athletes, one athlete Kickboxing, one athlete Karate and one athlete Muaythai. The instrument used in this research is the Bleep Test with classification norms using a bleep test calculator. Meanwhile, descriptive data analysis used SPSS 25 software. The results of this research for Taekwondo athletes were two above average, two were good. Wushu one average, one below average. Average kickboxing. Good karate. Muay Thai is average. In conclusion, Taekwondo athletes show a VO2 max that is generally higher compared to athletes from other disciplines. These results demonstrate the importance of personalized training programs to optimize cardiovascular fitness and performance in athletes. Further research with a more comprehensive approach is needed to strengthen and expand understanding of the influence of VO2 max on the performance of martial arts athletes.